Impact of peptide receptor radionuclide therapy (PRRT) on the 68Ga-DOTATOC-PET/CT uptake in normal tissue - Giesel, Frederik L.; Stefanova, Mesla; Afshar-Oromieh, Ali; Mier, Walter; Haberkorn, Uwe; Kratochwil, Clemens (The quarterly journal of nuclear medicine and molecular imaging, 2013)
1378 - Objectives PET/CT with [68Ga]DOTA0-Phe1-Tyr3-octreotide (68Ga-DOTA-TOC) became a standard for somatostatin receptor imaging. We investigated the potential changes of normal tissue uptake in patients with neuroendocrine tumor undergoing peptide receptor radionuclide therapy (PRRT). - Methods Sixteen patients underwent [68Ga]-DOTA-TOC-PET/CT prior and after 4-6 cycles of PRRT (mean administered activity: 13.8 GBq 90Y+ 9.6 177Lu). The maximum standardized uptake values (SUVmax) of pituitary, thyroid, spleen, liver parenchyma, pancreas, kidneys and adrenals were determined, respectively. - Results SUVmax values prior and after PRRT were in pituitary (5, 56±2,91/4,47 ±2,53), thyroid (2,05±1,11/2,49±2,47), spleen (24,95±14,20/20,06±8,53), liver (7,13±3,96/6,62±2,63), pancreas (6,96±1,99/6,83±2,00), kidneys (13,0±3,85/ 11,31±3,31) and adrenals (9,65±4,20/7,10 ±2,86). A comparison of pre- and post treatment values revealed no significant differences (p>0.05) in any of these organs. - Conclusions The uptake of [68Ga] DOTA-TOC in normal tissue is not significantly affected by PRRT. This is relevant with regards to therapeutic monitoring were tumor-to-non-tumor ratio seems to be the most robust biomarker. - Research Support The uptake of [68Ga]DOTA-TOC in physiological SSTR expressing organs such as pituary, thyroid and adrenal glands is not significantly affected by PRRT. Therefore, it seems that there is neither an acute nor chronic side effect for the physiological expression of SSTRs in endocrine organs at the upper limit of activity recommended for PRRT.
Gesehen am 12.03.2021
Im Titel ist die Zahl 68 hochgestellt